2021
DOI: 10.1097/ruq.0000000000000563
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Shear Wave Elastography in the Differentiation of Acute and Subacute Deep Venous Thrombosis

Abstract: It is important to know the age of clot formation to determine an appropriate treatment for deep vein thrombosis (DVT). The present study aims to differentiate between acute and subacute DVT using the shear wave elastography (SWE) technique. Patients with complaints no longer than 4 weeks and who were found to have early-stage (acutesubacute) thrombus on ultrasound (US) between January 2020 and May 2020 were included in the study. All of the patients underwent SWE using a Philips Healthcare EPIQ 5 Ultrasound S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
(71 reference statements)
0
9
0
2
Order By: Relevance
“…Sample ages examined here ranged from 1 to 30 days, with an average and standard deviation of 12.2 ± 9.8 days. The average elastic modulus may also not be a good metric because of sample inhomogeneity, though similar degrees of inhomogeneity is observed for clinical scans of DVT 77 , 78 . Ultrasound images are inherently two-dimensional, and volumetric assessment of the sample stiffness may provide a more applicable comparison to bulk measurements such as mass loss.…”
Section: Discussionmentioning
confidence: 96%
“…Sample ages examined here ranged from 1 to 30 days, with an average and standard deviation of 12.2 ± 9.8 days. The average elastic modulus may also not be a good metric because of sample inhomogeneity, though similar degrees of inhomogeneity is observed for clinical scans of DVT 77 , 78 . Ultrasound images are inherently two-dimensional, and volumetric assessment of the sample stiffness may provide a more applicable comparison to bulk measurements such as mass loss.…”
Section: Discussionmentioning
confidence: 96%
“…In a study of 50 cases, Durmaz and Gultekin 20 stated that determining the thrombus age plays a critical role in the prescription of a treatment in DVT and found a statistically significant difference between elastography values in the differentiation of acute and subacute thrombus. In our own study, we concluded that medical treatment was successful in acute thrombi with lower SWE values.…”
Section: Discussionmentioning
confidence: 99%
“…Further, using a cutoff value of 2.85, the sensitivity and specificity were 96.3% and 91.3% for acute DVT. 35 However, given the small sample size, further studies are warranted to validate these results.…”
Section: Sonographic Evaluation Of Venous Thrombotic Diseasementioning
confidence: 93%